Is Immunosuppressive and Thrombolytic Therapy Really Effective in a Patient With Intracardiac Thrombosis and Pulmonary Artery Aneurysm due to Behçet’s Disease? - Nükhet ALADAĞ ÇİFTDEMİR and Selman GÖKALP and Tuba EREN (Archives of Rheumatology, 2019)
Behçet’s disease (BD) is a rare, multisystemic, chronic vasculitic disorder with unknown etiology. Intracardiac thrombus formation and pulmonary artery aneurysm in BD are very rare. The treatment protocol in patients with vascular involvement, particularly those with pulmonary artery aneurysm accompanied by thrombosis, have not been clearly defined. In this article, we report an exceptional case, who had been treated unsuccessfully with a combination of anti-inflammatory/immunosuppressive therapy and thrombolytic agents, to discuss the poor prognosis of pulmonary artery aneurysm accompanying intracardiac thrombosis in juvenile BD.